Tools for harmonization of data in World‐Wide FINGERS - Talton, Jennifer W; Fernandez, Shane; Garcia, Katelyn R; Crivelli, Lucia; Snyder, Heather M; Lovato, Laura; Martins, Ralph N; Kivipelto, Miia; Mangialasche, Francesca; Pérez, Kristal Morales; Espeland, Mark A (ALZHEIMERS & DEMENTIA, 2021)
Background World‐Wide FINGERS (WW‐FINGERS) is a global network of multidomain lifestyle intervention trials for dementia risk reduction and prevention (Kivipelto et al., 2020). With over 30 countries conducting studies within the network, harmonizing interventions and data collection wherever possible is a priority. However, study‐specific adaptations are inevitable to accommodate differences in language, culture, and environment. Thus, a single data collection system is not feasible across WW‐FINGERS and opportunities for synergies between study‐specific systems should be explored. Method REDCap (Research Electronic Data Capture) is a secure, web‐based software platform which supports validated data capture for research studies (Harris et al., 2009). The underlying blueprint for each REDCap project is a ‘data dictionary’ – a .csv file containing all metadata required to recreate case report forms (CRF) for each point of data collection, including variable names and response options. Data dictionaries can be easily exported, shared, and imported into other REDCap instances. This enables utilization of the same overall structure where possible and preserves response options and variable names while making needed adaptations. Within the WW‐FINGERS network, the study to Protect Brain Health through a Lifestyle Intervention to Reduce Risk (U.S. POINTER) developed a REDCap system based on its protocol and shared its data dictionary with two other WW‐FINGERS studies – AUstralian‐Multidomain Approach to Reduce Dementia Risk by PrOtecting Brain Health with Lifestyle Intervention (AU‐ARROW) and LatAm FINGERS (Latin American initiative for lifestyle Intervention to Prevent Cognitive Decline and reduce risk study). Result AU‐ARROW and LatAm FINGERS are in the process of incorporating relevant pieces of the U.S. POINTER REDCap project into REDCap systems developed for their studies. While the systems are not identical given the different intervention structures, we aim to standardize 50‐75% of the common variables used across the studies. Conclusion Using REDCap allows each WW‐FINGERS study to develop its own customized system for data capture, while easily standardizing common variable names, response options, and CRFs; along with exporting de‐identified data. As a result, data sharing and analysis across the WW‐FINGERS network can be streamlined. Furthermore, this process may serve as a roadmap for other global consortia’s similar efforts.